Educational Trip With Teeth Doll to Promote Dental Health in Preschool-Age Children - Diah Sulistyowati (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
The case of children with dental caries in 2017 was found at 79.8 percent and 82.83 percent in 2018 in Public Health Center Cibeber. Preschool-age children visit dental poly in 2018 only 206 children from approximately 1,536 children. Dental caries in a childcause cavities, pain, sleep disorders, and broken teeth, which can cause food absorption disorders that will affect child's growth and development delay, it can decrease child's level of intelligence, so preschool-age children's awareness of the importance of dental and oral health needs to be increased. Innovative dental health promotion by making the health care as a trip vacation, it was an Educational Trip with Teeth Doll or an E-Bogi Trip. To analyze the innovation of E- Bogi Trip as an effort to promote dental health in preschool-age children used qualitative descriptive methods, research in March through December 2019, at Public Health Center Cibeber Cilegon City, uses a purposive sampling with a deep study analysis technique. E-Bogi Trip has matched the characteristics of innovation, having interesting ideas with visual media and teeth doll, has a new idea of health promotion, good planning with the governing support, cross programs, cross sectors and the goals of that innovation can be achieved. Innovation was done well, seen from the increase in preschool-age visits to dental poli in 2019 to 395 children and 569 preschool-age children have an ability on dental care. It’s was matched the characteristics of innovation and can increase efforts to promote preschool-age children's dental health, which is expected to achieve good dental health and can develop optimally.